Passer, a highly active transposon from a fish genome, as a potential new robust genetic manipulation tool. Issue 4 (23rd January 2023) - Wang, Saisai; Gao, Bo; Miskey, Csaba; Guan, Zhongxia; Sang, Yatong; Chen, Cai; Wang, Xiaoyan; Ivics, Zoltán; Song, Chengyi
Abstract: The discovery of new, active DNA transposons can expand the range of genetic tools and provide more options for genomic manipulation. In this study, a bioinformatics analysis suggested that Passer ( PS ) transposons, which are members of the pogo superfamily, show signs of recent and current activity in animals and may be active in some species. Cell-based transposition assays revealed that the native PS transposases from Gasterosteus aculeatus and Danio rerio displayed very high activity in human cells relative to the Sleeping Beauty transposon. A typical overproduction inhibition phenomenon was observed for PS, and transposition capacity was decreased by ∼12% with each kilobase increase in the insertion size. Furthermore, PS exhibited a pronounced integration preference for genes and their transcriptional regulatory regions. We further show that two domesticated human proteins derived from PS transposases have lost their transposition activity. Overall, PS may represent an alternative with a potentially efficient genetic manipulation tool for transgenesis and mutagenesis applications.